44. ENHANCING HEALTHCARE WORKERS' KNOWLEDGE OF PATIENT SAFETY AND INFECTION CONTROL THROUGH TARGETED TRAINING AT DIEN BIEN PROVINCIAL GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Aim: To assess the effectiveness of targeted interventions to improve health care workers (HCWs)' knowledge of COVID-19 patient safety at Dien Bien Provincial General Hospital.Methods: A pre- and post-intervention study was conducted among 275 full-time HCWs at Dien Bien Provincial General Hospital from July 2021 to July 2022. Participants attended five structured training sessions focused on patient safety and COVID-19 prevention, including personal protective equipment (PPE) use and hand hygiene. Knowledge was measured using a questionnaire based on Vietnam’s Ministry of Health patient safety guidelines. Data were analyzed using SPSS 22.0, with statistical significance set at p < 0.05.Results: The intervention led to significant improvements in HCWs’ knowledge of COVID-19 prevention measures. Compliance with mask-wearing increased from 86.9% to 92.7%, and knowledge scores for infection control measures rose substantially. Standard precautions improved from 72.0% to 85.1%, and transmission-based precautions from 47.6% to 76.4%. Mean knowledge scores increased across general prevention (1.71 to 1.81), infection control (2.87 to 3.90), and laundry handling (5.32 to 6.29) domains.Conclusion: The targeted training interventions successfully increased HCWs' adherence to essential COVID-19 prevention protocols, demonstrating the potential of similar programs to improve healthcare safety in Vietnam. Continuous education is recommended to sustain high compliance and address logistical barriers in infection control practices.
Keywords: COVID-19 prevention; patient safety; healthcare workers; safety protocols; community intervention